A lasting antibacterial, pro‐angiogenic, and pro‐osteogenic zirconium‐based bulk metallic glass for dental implants - Feifei Wang; Yunshu Wu; Fu Zheng; Yuhao Zeng; Zifan Zhao; Yao Huang; Xu Zhang; Baoan Sun; Yuchun Sun (View)
Abstract Bacterial infection and mismatched mechanical properties are important factors that increase the risk of dental implant failure. However, zirconium (Zr)‐based bulk metallic glasses (BMGs) can have both high strength and low modulus, as well as good biocompatibility, due to their unique atomic arrangement structure. Based on these common characteristics, different elemental compositions can endow zirconium‐based amorphous alloys with different properties. Here, we present a Zr‐based BMG containing silver (Ag) with good amorphous process ability, exhibiting lasting antibacterial, proangiogenic, and pro‐osteogenic properties. This newly developed Zr61Cu23Al12Ti2Ag2 (at.%) BMG has higher strength and lower modulus than pure Titanium (Ti). Furthermore, it could exert antibacterial effects through both contact inhibition and metal ion sterilization. And this antibacterial property could last over 3 months. The systematically in vitro and in vivo results thus demonstrate the advantages and application potentials of Zr‐based BMG as a highly promising oral implant material for dental implantation.